2013
DOI: 10.1371/journal.pone.0074395
|View full text |Cite
|
Sign up to set email alerts
|

Flower Colour Modification of Chrysanthemum by Suppression of F3'H and Overexpression of the Exogenous Senecio cruentus F3'5'H Gene

Abstract: Chrysanthemum (Chrysanthemum × morifolium) is one of the most important ornamental plants in the world. They are typically used as cut flowers or potted plants. Chrysanthemum can exhibit red, purple, pink, yellow and white flowers, but lack bright red and blue flowers. In this study, we identified two chrysanthemum cultivars, C × morifolium ‘LPi’ and C × morifolium ‘LPu’, that only accumulate flavonoids in their ligulate flowers. Next, we isolated seven anthocyanin biosynthesis genes, namely CmCHS, CmF3H, CmF3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 51 publications
(61 reference statements)
3
36
0
Order By: Relevance
“…By expressing genes in the Petunia that were deficient in the F3 ′ H and F3 ′ 5 ′ H genes, Tanaka reported that the CYP75 members from cineraria are F3′H and F3′5′H (Tanaka and Brugliera, 2013). However, in accordance with our previous studies, the results from our gene expression and HPLC analysis show that the content of Dp was much higher than Cy in JeB, suggesting that there is a very high CYP75A activity of ScF3 ′ 5 ′ H (Huang et al, 2013; Sun et al, 2014). …”
Section: Discussionsupporting
confidence: 93%
“…By expressing genes in the Petunia that were deficient in the F3 ′ H and F3 ′ 5 ′ H genes, Tanaka reported that the CYP75 members from cineraria are F3′H and F3′5′H (Tanaka and Brugliera, 2013). However, in accordance with our previous studies, the results from our gene expression and HPLC analysis show that the content of Dp was much higher than Cy in JeB, suggesting that there is a very high CYP75A activity of ScF3 ′ 5 ′ H (Huang et al, 2013; Sun et al, 2014). …”
Section: Discussionsupporting
confidence: 93%
“…The two genes are closely related, having diverged from a common ancestor, and reversals of function are known in nature (Seitz et al 2006). Senecio cruentus F3′5′H for instance, when transformed into Chrysanthemum, fails to produce delphinidin but increases cyanidin production (He et al 2013). What is more surprising is the complete lack of delphinidin production by wild-type Lathyrus F3′5′H when transformed into Arabidopsis background.…”
Section: Discussionmentioning
confidence: 99%
“…(iii) Arabidopsis is not an appropriate host for sweet pea F3′5′H for reasons other than the lack of a suitable reductase suggested above. Studies have shown that gene origin is important to the successful transformation of F3′5′H with some host-donor pairs more successful in producing delphinidin-series than others (Okinaka et al 2003;Katsumoto et al 2007;He et al 2013). One possibility is that substrate specificity for DFR is different between sweet pea and the Arabidopsis host.…”
Section: Discussionmentioning
confidence: 99%
“…These structural genes play an important role in the synthesis and accumulation of anthocyanins and the homologues genes have been isolated in many ornamental plants including Petunia, Chrysanthemum, Gentiana, Gerbera, and Torenia (Koes et al, 1986;Van Tunen et al, 1988;Nakamura et al, 2006;Wellmann et al, 2006;Nakatsuka et al, 2008;He et al, 2013). Meanwhile, genetic engineering of flower color has been achieved through transgenic experiments.…”
Section: Lathyroides (Lath) Wox1mentioning
confidence: 99%